Intimate partner violence during pregnancy among married women in Putalibajar municipality, Nepal - Sharma, Rakshya; Kaphle, Hari Prasad (Frontiers in Psychology, 2023)
Introduction Intimate partner violence during pregnancy (IPVDP) is increasingly being recognized as a significant problem in the developing world due to its adverse health consequences on both pregnant women and children. The objective of the study is to measure the magnitude of intimate partner violence during pregnancy and the factors associated with IPVDP. Methods A community-based cross-sectional study was conducted among 263 married women in their extended postpartum period between October 2019 and March 2020 in Putalibajar municipality, Nepal. A face-to-face interview was conducted and data were collected using an interview schedule. A Chi-square test and logistic regression analysis were performed to examine the association between IPVDP and the independent variables. Results Among the 263 women interviewed, 30% experienced IPV during pregnancy, the most common type of violence was controlling behavior (20.2%) followed by emotional (18.6%), sexual (10.6%), economic (6.1%), and physical violence (5.3%). It was observed that IPV was more likely to occur among women whose husbands consumed alcohol (AOR = 3.171; CI 95%: 1.588–9.167), women whose husbands consumed tobacco (AOR =3.815; CI 95%: 2.157–7.265), women who sometimes received family support during pregnancy (AOR =2.948; CI 95%: 1.115–7.793) and women who did not decide on marriage timing (AOR =2.777; CI 95%: 1.331–5.792). Conclusion Three out of ten pregnant women experienced IPVDP. To prevent violence, and ensure women’s empowerment, formulating strict laws and discouraging the element of a violent milieu is important.